Learning the Intrinsic Elements of the East Kalimantan Folklore "The Story of Si Pego" through a Dual Strategy Using Special Modules - Mulajmi Ramli; Alfian Rokhmansyah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to explore: 1) the learning procedure of the intrinsic elements of the East Kalimantan folklore 'Kisah Si Pego' using a dual strategy through a special module; 2) the learning outcomes of the intrinsic elements of the East Kalimantan folklore 'Kisah Si Pego' using a special module. This study took place at the beginning of the odd semester of the 2025/2026 academic year at SMP Negeri 10 Penajam Paser Utara. The population was a group of 7th grade students who participated in learning the intrinsic elements of the East Kalimantan folklore 'Kisah Si Pego' using the cloz technique through a special module. They numbered 66 students in two parallel 7th grades; each class served as a control class and a treatment class. The sample of this study was all members of the population. The first instrument was an observation guideline that served to collect data on the learning procedure. The second instrument was a written test in the form of 4 multiple-choice options about the intrinsic elements of the folklore. Learning data were analyzed thematically while learning outcome data were analyzed using descriptive statistical procedures. The results of the study: 1) the learning procedure for the intrinsic elements of the East Kalimantan folklore 'Kisah Si Pego' uses a dual strategy through a special module containing 3 types of initial activities; 2) the learning procedure for the intrinsic elements of the East Kalimantan folklore 'Kisah Si Pego' uses a dual strategy through a special module containing 13 core activities; 3) the learning procedure for the intrinsic elements of the East Kalimantan folklore 'Kisah Si Pego' uses a dual strategy through a special module containing 2 types of final activities; 4) the learning outcomes of the intrinsic elements of the East Kalimantan folklore 'Kisah Si Pego' using a dual strategy through a special module reached a mean of 83.23 in the treatment class and 70.57 in the control class.